Secret of the Masters: Young Chess Players Show Advanced Visual Perspective Taking - Gao, Qiyang; Chen, Wei; Wang, Zhenlin; Lin, Dan (Frontiers in Psychology, 2019)
Playing chess requires perspective taking in order to consistently infer the opponent’s next moves. The present study examined whether long-term chess players are more advanced in visual perspective taking tasks than their counterparts without chess training during laboratory visual perspective taking tasks. Visual perspective taking performance was assessed among 11- to 12-year-old experienced chess players (n = 15) and their counterparts without chess training (n = 15) using a dot perspective task. Participants judged their own and the avatar’s visual perspective that were either consistent with each other or not. The results indicated that the chess players out-performed the non-chess players (Experiment 1), yet this advantage disappeared when the task required less executive functioning (Experiment 2). Additionally, unlike the non-chess players whose performance improved in Experiment 2 when the executive function demand was reduced, the chess players did not show better perspective taking under such condition. These findings suggested that long-term chess experience might be associated with children’s more efficient perspective taking of other people's viewpoints without exhausting their cognitive resources.